A new variety of Ipomoea cairica (Convolvulaceae) from Karnataka, India - Anasuya; Shivamurthy, G R; Murali, M; Thriveni, M C; Amruthesh, K N (Plant Science Today, 2025)
Ipomoea L. is a species-rich genus in the family Convolvulaceae, widely distributed across temperate and tropical regions of the world. Due to its wide distribution and morphological variability, identifying and classifying Ipomoea species has become challenging. The present study attempts to classify species within the genus Ipomoea based on morphological features, with a particular focus on floral characters, which serve as useful diagnostic traits for identification. This study specifically focuses on I. cairica (L.) Sweet, commonly known as ‘blue morning glory,’ a wide spread species within the family. It is characterized by a campanulate glabrous corolla, a key floral feature. However, in the present investigation, additionally a distinct characteristic wing like appendages on the outer part of petals was observed in the flowers of I. cairica. This trait suggests a divergence in habitat preference and points to the possible evolution of a new variety. Based on careful observation over four generations, it is concluded that a putative variety of I. cairica has emerged, consistently exhibiting these unique features. Consequently, it is elevated to the rank of a new variety, named I. cairica var. appendiculata, from Karnataka, India. A detailed description, illustration and an artificial key for the new variety are provided.